The use of diuretics in heart failure with congestion: we can't judge a book by its cover - Palazzuoli, Alberto (ESC Heart Fail, 2019)
Although congestion assessment is one of the major challenges in the management of acute heart failure (AHF), no specific Gguidelines have been previously published on this topic. A recent position paper from ESC HF society, focused attention on targeting therapy in relation to clinical congestion. However, in our opinion, the scarce correlation existing between wedge pressure with and traditional clinical signs is the fundamental concern in congestion detection. The two main characteristics of congestion are redistribution of blood volume from the systemic to the pulmonary district and intravascular fluid retention, and both of these are often employed with different significance. Another weakness could come from the varied congestion appearance in relation to the clinical scenario: the different pattern could vary in relation to prevalent cardiac dysfunction ([i.e. heart failure with reduced ejection fraction [(HFrEF]) vs. heart failure with preserved ejection fraction [(HFpEF)]), the Stevenson picture, and the history of recurrent or de novo HF. Thus, it could be worth distinguishing between central and peripheral congestion, in relation to the involved sites and organ damage. Our advice for a more effective diuretic dose is to obtain a better assessment of congestion by an integration between the clinical examination and a diagnostic algorithm taking into account echo and laboratory parameters. Consequently, the use of intravenous diuretics needs to be tailored in relation to the severity of congestion, the oral administration amount, and the different HF profiles.